'Crude' Alliance – Economic Decolonisation and Oil Power in the Non-Aligned World. (November 2021) - Spaskovska, Ljubica
Abstract : The article examines Yugoslavia's and by extension the Non-Aligned Movement's relations with the Middle East, reflecting more broadly on the developmental hierarchies and inner divides between the oil producing and non-oil producing countries within the Movement. The 'energy shocks' of the 1970s had a dramatic impact on non-OPEC developing countries and sowed long-lasting rifts in the non-aligned/developing world. The article embeds these events within the debates about the 'New International Economic Order' (NIEO), economic decolonisation and the nationalisation of energy resources in the 1970s, but also seeks to provide a longer-term overview of the economic and political relations that non-aligned Yugoslavia sought to forge with the Middle East, in particular with other non-aligned partners such as Egypt, Iraq, Libya and Kuwait. New forms of Cold War developmental multilateralism emerged as a consequence of the energy crisis – the supply of Arab oil to areas which had traditionally relied on Soviet energy not only foreshadowed the emergence of a new hierarchical and dependent relationship between Yugoslavia and the Middle East, it also engendered new forms of economic cooperation and strategic economic multi-alignment through the pooling of resources and expertise from non-aligned, Eastern Bloc states and the United Nations, illustrated here through the Adria Oil Pipeline built in the 1970s and co-financed by Yugoslavia, Kuwait, Libya, Hungary, Czechoslovakia and the World Bank.